117k views
12 votes
Help fast and thanks and whoever's reading this have a nice night​

Help fast and thanks and whoever's reading this have a nice night​-example-1
User Hazzu
by
5.0k points

1 Answer

12 votes

Answer:

Explanation:

7)
n-(8)/(9)=(4)/(9)


n-(8)/(9)+(8)/(9) =(4)/(9)+(8)/(9)

n =
(4+8)/(9)

n =
(12)/(9)

n =
(4)/(3)

8).
(3)/(2)+x=-(7)/(2)


(3)/(2)+x-(3)/(2) =-(7)/(2)-(3)/(2)

x =
-(7+3)/(2)

x = -5

9).
(6)/(5)= (d)/((5)/(4))

d =
(6)/(5)* (5)/(4)

d =
(6)/(4)

d =
(3)/(2)

10).
-(1)/(8)V=(5)/(2)


-(1)/(8)V* (-8)=(5)/(2)* (-8)

V = -20

User Phil Loden
by
5.1k points